Peningkatan Hasil Belajar Siswa Pada Materi Penyajian Data Menggunakan Model Kooperatif Tipe Jigsaw - Melati, Melati; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to improve the learning outcomes of presenting data using a Jigsaw cooperative model in class V SDN 07 Padang Sarai Kec. Lubuk Sikaping. This type of research is classroom action research using qualitative and quantitative approaches. Subjects in the study were fifth grade students of SDN 07 Padang Sarai Sub-district Lubuk Sikaping, amounting to 20 people, consisting of 10 men and 10 women. The research instrument uses test sheets, non tests and observations and the data analysis techniques used are descriptive qualitative and quantitative. The results showed that using a Jigsaw cooperative model can improve student learning outcomes in data presentation material.